Антология выдающихся достижений в науке и технике. Часть 31: Портрет харьковского физика Александра Ильича Ахиезера - Баранов, Михаил Иванович (НТУ "ХПИ", 2016)
Приведен краткий научно-исторический очерк об известном физике-теоретике Харьковщины - академике АН УССР (НАН Украины) Ахиезере А. И. и его выдающемся вкладе в мировую физическую науку.

Short information is resulted about the basic creative and vital stages, and also fundamental scientific achievements of the indicated prominent physicist of the 20th century. Some personal qualities of this Kharkiv theoretical physicist, becoming a founder known in the world of physical school are described.
An antology of the distinguished achievements in science and technique. Part 31: Portrait of the Kharkiv physicist Alexander Ilyich Akhiezer
Keywords: Харьковщина; история; физика; Institute of Physical Problems; UPTI; Kharkiv region; physics; history